Design of floating solar PV system for typical household on Debre Mariam Island. Issue 1 (1st January 2020) - Taye, Biniyam Zemene; Nebey, Abraham Hizkiel; Workineh, Tewodros Gera
Abstract: Solar PV is possible alternative renewable energy resources, particularly for rural electrification. Its high demand growth may cause for land scarcity, and this will be a serious problem in countries like Ethiopia where agriculture is main source of economy and population large size. In addition to land scarcity, low efficiency of photovoltaic land installation is another problem. Hence, photovoltaic performance is relying on weather conditions, operation parameters like temperature and wind speed. Water bodies can be alternatives to install photovoltaic to the scarcest land and decrease impact of temperature on photovoltaic. To reduce the affirmation problems floating system is an alternative technology. Floating photovoltaic plants are an emerging form of PV system that floats on water bodies. Land installation of photovoltaic increases risk of PV module efficiency drops land scarcity. Therefore, the objective of this study was to design floating system for Debre Mariam Island to increases efficiency of solar cell and save land. To tackle mentioned problems floating photovoltaic installation is method used. Floating photovoltaic provides efficient energy supply and new strategy to save land. Thus, floating photovoltaic system is modeled so as to satisfy daily energy load demand of Debre Mariam Island community electric loads. The temperature and wind speed are major contributory factors for panel efficiency drops and low power output in land photovoltaic installations. 294.8 kW is the generated power output of solar floating system whereas 289.9 kW is the generated power output of land photovoltaic installation. Thus, floating PV installation increases the generated power output by 4.9 kW.